PRARANCANGAN PABRIK METIL ISO BUTIL KETON DENGAN BAHAN BAKU ASETON DAN HIDROGEN KAPASITAS 75.000 TON/TAHUN - , MAHARDITA CAHYUNINGTYAS, Prof. Ir. Arief Budiman, M.S., D.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Preliminary Design of Methyl Iso Butyl Ketone Plant was performed to investigate more about the feasibility of the plant to set up. Methyl Iso Butyl Ketone Plant is designed with Methyl Iso Butyl Ketone as the main product with a capacity of 75,000 tons/year and operate continuously for 24 hours/day and 330 days/year. To meet the production capacity annually, it takes as many as 96% of acetone 129.976,2288 ton/year and hydrogen gas as much as 1.624,6724 tons/year. While the needs of other supporting materials, such as a solution of NaOH 40%, Water, Aqueous H2SO4 is 98%, Nickel Catalysts, and Chloroform are respectively 43,7723 tons/year, 218,8549 tons/year, 282,0003 tons/year 750,0002 tons/year, and 7.537,6881 tons/year. Process of making Methyl Iso Butyl Ketone use three-step process, where the first stage is condensation Acetone be Diaseton Alcohol with the help of a catalyst solution NaOH 40 % in Reactive Distillation-01.The second stage is reaction dehydration Diaseton Alcohol be Mesityl Oxide with the help of a catalyst solution H2SO4 98 % in Reactive Distillation-02. And the last stage is reaction hydrogenated Mesityl Oxide be Methyl Iso Butyl Ketone using catalysts of nickel in Slurry Reactor. Methyl Iso Butyl Ketone plant will be established in the industrial area of Cilegon, Banten, with a land area of 59,000 square meters and employs more than 219 employees. Electricity used in this factory supplied by PLN of 2.223.590,998 kWh/year. The fuel needs at this factory of 864,2344 US gallons/hour and will generate free heat in the reboiler of 78.308.936,72 Btu/hour. Water needs in this factory of 30.930,11 kg/hour and to meet the needs of water at this plant, water supply is obtained from the Cidanau River which is located quite close to the factory. To run production at this factory, it takes a fixed capital of $ 15,065,617.03 + Rp 70.296.759.501,48and working capital of$ 8,887,229.92 + Rp 223.275.077.768,26. Methyl Iso Butyl Ketone plant is relatively high risk with the ROI before tax 50,96%, POT before tax 1,64 years, BEP 45,65%, SDP 31,79%, and DCFRR 25,21%. Based on the values above, it can be concluded that the factory is economically interesting and deserved to be examined further.